Microstructural characterisation of brittle fracture initiation sites in reactor pressure vessel steels - Paul Chekhonin; Aniruddh Das; Frank Bergner; Eberhard Altstadt (Nuclear Materials and Energy, 2023)
Neutron embrittlement of reactor pressure vessel (RPV) steels potentially limits the safe operational time of nuclear reactors. In tested RPV steel samples microcracks are known to originate from cleaved precipitates, inclusions or grain boundaries, which eventually lead to brittle fracture. In most cases, these precipitates are reported as carbides. Latest research indicates the critical fracture event to be the crossing of grain boundary instead of the particle–matrix interface by the microcrack. Very few works have performed detailed fractography, which revealed the size and type of the feature found in the crack nucleation centre, together with metallographic bulk investigations. Additionally, the effect of subsequent neutron irradiation on microcrack nucleation is unknown. In the present work, detailed fractography and metallography is performed on a RPV steel in both its unirradiated as well as neutron irradiated state. A particle in the centre of the initiation site has been identified in a majority of the cases, while no specific type of particles were involved in more than 1/3 of all samples. Those particles are either Mo-rich carbides or Al-rich inclusions. In comparison, the metallographic analysis of the bulk steel reveals Mo-rich and Mn-rich carbides. Mn-rich carbides constitute the majority of all carbides in the steel but are never found to be responsible for brittle fracture initiation. Only a small fraction of observable carbides is Mo-rich which are responsible for fracture. Thus, the present work demonstrates a discrepancy between particles found in brittle fracture initiation sites and particles that are directly observable in bulk steel. Some of the initiating particles are extremely rare in the bulk. Furthermore, it is revealed that the local fracture stress does not depend on the type or size of particle or grain involved at the initiation site. In conclusion, the fracture stress strongly depends on the type of the grain boundary, rather than on a stress based upon a Griffith criterion, which considers particle or grain size alone. The brittle fracture mechanism was found to be unaffected by neutron irradiation. These findings could help refine modelling of the critical brittle fracture stress and fracture toughness using microstructural parameters as input.